2021
DOI: 10.2217/fon-2021-0996
|View full text |Cite
|
Sign up to set email alerts
|

The 31-gene expression profile stratifies recurrence and metastasis risk in patients with cutaneous melanoma

Abstract: Aim: Sentinel node biopsy is a prognostic indicator of melanoma recurrence. We hypothesized that adding the primary melanoma molecular signature from the 31-gene expression profile (31-GEP) test could refine the risk of recurrence prognosis for patients with stage I–III melanoma. Materials & methods: Four hundred thirty-eight patients with stage I–III melanoma consecutively tested with the 31-GEP were retrospectively analyzed. The 31-GEP stratified patients as low-risk (Class 1A), intermediate-risk (Class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The 31-GEP test was developed and validated through gene expression analysis using RT-PCR and radial basis machine learning to provide a risk score from 0-1.0 with reproducible test results during analytic validation, 16,31 has been validated in multiple retrospective and prospective studies, and has been shown to influence treatment decisions in 50% of cases. [6][7][8]10,17,32,33 The 31-GEP has been integrated with clinical and pathological factors using a neural network algorithm to provide an individualized, precise risk of SLN positivity (i31-GEP). 12 Of the variables included in the i31-GEP neural network, the 31-GEP risk score was the most significant contributor to the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 31-GEP test was developed and validated through gene expression analysis using RT-PCR and radial basis machine learning to provide a risk score from 0-1.0 with reproducible test results during analytic validation, 16,31 has been validated in multiple retrospective and prospective studies, and has been shown to influence treatment decisions in 50% of cases. [6][7][8]10,17,32,33 The 31-GEP has been integrated with clinical and pathological factors using a neural network algorithm to provide an individualized, precise risk of SLN positivity (i31-GEP). 12 Of the variables included in the i31-GEP neural network, the 31-GEP risk score was the most significant contributor to the model.…”
Section: Discussionmentioning
confidence: 99%
“…The test analyzes the expression of 31-gene targets and has been validated as a statistically significant predictor of recurrence, distant metastasis, and death, independent of other clinical and pathological features. [6][7][8][9][10][11] The 31-GEP continuous risk score has been integrated with clinical and pathological features (Breslow thickness, mitotic rate, ulceration, and age) using a neural network algorithm to determine a precise risk score for SLN positivity (i31-GEP SLNB) and the 31-GEP score was a significant and independent contributor. 12 The i31-GEP algorithm for SLNB was shown to provide benefit for selecting patients for SLNB over treating all with SLNB.…”
mentioning
confidence: 99%
“…After screening the articles, 32 met inclusion criteria and were distributed to the panelists for review prior to the roundtable discussion. Of these articles, the number of papers that specifically studied the validity, accuracy, or clinical utility of each test was: 22 for the 31-GEP test 4,[19][20][21][22][23][24][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42] , 2 for the 11-GEP test 11,34 , and 7 for the 8-GEP + CP test. 5,13,23,[43][44][45][46]…”
Section: Comprehensive Literature Searchmentioning
confidence: 99%
“…For the 8-GEP + CEP test, a validation study analyzing the test's ability to predict SLNB positivity found that this model has a NPV of 90.5% (95% Confidence Interval [CI]: 77.9-96.2%) in T1-4 CMs. 44 In comparing the three GEP tests, the panel consensus was that there were significantly more studies supporting the validity, accuracy, and clinical utility of the 31-GEP test compared to the 11-GEP and 8-GEP + CP tests (22 studies validating the 31-GEP test 4,[19][20][21][22][23][24][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42] , compared to just 2 studies validating the 11-GEP test 11,34 and 7 studies validating the 8-GEP + CP test 5,13,23,[43][44][45][46] ). Based on the limited studies for the 8-GEP + CP and the 11-GEP test, the panel concluded that there was insufficient data to assess their validity and utility or currently recommend usage in the clinical setting until further studies are performed.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…The 31-gene expression profile test (31-GEP; DecisionDx-Melanoma, Castle Biosciences, Friendswood, TX) for cutaneous melanoma has been validated across numerous independent prospective and retrospective studies and meta-analyses as an independently significant molecular risk stratification tool to identify patients at high and low risk of recurrence or metastasis. [13][14][15][16][17][18] Moreover, when combined with T-stage and patient age, the 31-GEP model identifies a group of patients with <5% risk of SLN positivity who have high survival rates and can likely safely forego SLNB. 19 The 31-GEP has been analytically validated, showing high reproducibility and confidence in the obtained result.…”
mentioning
confidence: 99%